Three Year's of Financial Review and Performance Appraisal of Madhya Pradesh State Forest Development Corporation Ltd. - Seth, V. K.; Jaju, N. D. (Indian Forester, 1979)
Corporate planning is an attempt to ensure that Managers are continually measuring their performance against the Company's long-term profit and market objectives, evaluating alternative methods of reaching their goals and keeping in touch with rapid changes in the market as well as techniques. Profit is the criterion of efficiency. In the State undertakings, social objectives are more important than profit. The MP State Forest Development Corporation aims at generating employment in the remote and under-developed areas not only to improve the standard of living of the tribal people, but also to ensure rapid economic growth by building up required infrastructure. This publication deals with financial review, profitability analysis and performance appraisal in relation to corporate objectives and socio-economic aims of MP State Forest Development Corporation. The performance appraisal should aim at finding out if the existing forest produce has been exploited as economically and expeditiously as possible and as to whether the same has been prudently replaced by raising successful plantations of economically valuable and useful species,in addition to its financial liquidity and return on capital. The study is an attempt to present for a three year period of Corporation's existence, planting performance, productivity and profit analysis, economic growth and finacial visibility, profitability and return on capital employed, financial break up of revenue expenses in relation to value of production, funds utilisation analysis,employment generation and review of staff expenses.